The influence of rotor/wing aerodynamic interaction of compound helicopter in forward flights on wing-body - Hamamoto, Y.; Akasaka, T.; Tanabe, Y.; Sugawara, H. (My University, 2022)
This paper investigates the influence on aerodynamic characteristics of a winged-body of a rotor/winged-body configuration due to changes of the advance ratio through numerical simulations. A winged compound helicopter has a single main rotor and a fixed-wing located under the rotor. Due to the configuration, an aerodynamic interaction occurs between the rotor and the wing. In high advance ratio flight, the aerodynamic interaction produces asymmetrical aerodynamic characteristics on the left and right sides of the wing. This phenomenon is dependent on the rotor flow field and is presumed to be changed by the advance ratio. Therefore, in this paper, the asymmetrical aerodynamic characteristics of the wing were investigated for advance ratio from 0.1 to 0.7. A computational model is constituted by the UH-60A main rotor only the blades and the winged-body. The winged-body combines a rectangle wing and a fuselage designed by JAXA. The wing has span length that of 0.7 times of the rotor diameter and an aspect ratio of 10. The rotor speed was scheduled to decrease along with increasing flight speed. The combination for this simulation was selected from the schedule in order to correspond to the advance ratio from 0.1 to 0.7. As a result, the lift coefficient, drag coefficient and lift-to-drag ratio of both sides on the wing of the rotor/winged-body configuration becomes closer to that of the isolated winged-body as the advance ratio increases, but that of the right side, witch is under the advancing side of the rotor, remains different to that of the isolated winged-body. The influences on the lift and drag coefficient are stronger at the root than the tip on the wing, at the right side more than the left side and at low advance ratio than at high advance ratio.